Myoanatomy of Myzostoma cirriferum (Annelida, Myzostomida): Implications for the evolution of the myzostomid body plan. (13th June 2013) - Helm, Conrad; Weigert, Anne; Mayer, Georg; Bleidorn, Christoph
Abstract Cover illustration. The morphological transformation of hermit crabs into king crabs represents one of the evolutionary most fascinating scenarios in decapod evolution. It is certainly the most remarkable case of carcinization, or evolutionary shaping into a crab‐like form. In this issue of the Journal of Morphology Keiler and coauthors (pp. 759–778) investigate the hemolymph vascular system and adjacent anatomical structures of several recent hermit crab (Paguridae) and king crab (Lithodidae) species. The cover image shows a dorsal view of a corrosion cast of the circulatory system in Paralomis granulosa catched in the Pacific off the coast of Chile (Photograph by Jonas Keiler).